Diversitas dan Potensi Jamur Lignolitik Asal Seresah Daun - Arif Rahman Hikam; Dwiana Muflihah Yulianti; Rhevi Raditya Ginanjar (Al-Hayat: Journal of Biology and Applied Biology, 2021)
One of the biological agents in the biodegradation of organic waste is fungi. Some fungi have the Lignase enzyme, which can degrade Lignin (one of the main organic waste constituents) into simple sugars. The diversity and potential of organic waste degrading fungi still need much research to obtain potential types of fungi that can be developed in organic waste management. This study aimed to determine the diversity and potential of lignolytic fungi in the biodegradation of organic waste. The research was conducted using a descriptive method to take leaf and soil litter samples, isolate and purify fungi, and test lignolytic potential. Based on the isolation results from leaf litter samples, 16 types of fungal isolates were obtained. The lignolytic potential test was carried out using the Bavendamm method. In screening for potential lignolytic ability using the bavendamm method, 7 isolates were found to be positive. The highest lignolytic activity ratio was SR4BD isolate with a ratio value of 1.9. The results showed that the SR4BD isolate was Fusarium sp.